First record of the genus Kliopsyllus Kunz, 1962 (Copepoda Harpacticoida, Paramesochridae) from Northeastern Brazil with description of the deep-sea species Kliopsyllus minor sp. nov. - Vasconcelos, Danielle Menor; Veit-Köhler, Gritta; Drewes, Jan; Santos, Paulo Jorge Parreira Dos (Zootaxa, 2009)
Sediment samples were collected from the deep sea adjacent to the State of Sergipe (Northeastern Brazil) within the framework of the Sergipe Continental Slope Environmental Characterization Project (coordinated by PETROBRAS, the Brazilian Petroleum Company S/A). These revealed a new species of the family Paramesochridae (Copepoda, Harpacticoida). Kliopsyllus minor sp. nov. is the smallest species discovered in this genus, with a body length of 0.19 mm in the adult male. Furthermore, it is one of the three Kliopsyllus species registered from the deep sea so far. In almost all Kliopsyllus species, the endopod of P4 is one-segmented. Only three species, i.e. Kliopsyllus andeep Veit-Köhler, 2004 from the abyssal Weddell Sea, a new species by Veit-Köhler and Thistle from the San Diego Trough (deep Pacific Ocean) and the new species presented here, show a two-segmented endopod in the P4. Kliopsyllus andeep is distinguished by the presence of strong, chitinous processes at the telson, and additional setae at the endopods of P3 and P4. The new Pacific species and the new species from Brazil can be distinguished by the shape of the segments of the swimming legs and detailed characteristics of their setae and spines.